Anti-formation strategies: the present of dystopia - Gramigna, Anita (Formazione & insegnamento, 2018)
The conviction that orients our analysis is that some famous narrative dystopias of the twentieth century have sensed, with “prophetic” sensitivity, the growing illness of western civilization that materialised itself in totalitarianisms which, as such, are neither left nor right. As we shall try to demonstrate, the fragility of the democratic fabric has been accompanied by a substantial crisis of formation, which can be seen in the symbols of the destruction of books or in the linguistic reductionism for the single thought’s propagandistic ends. For our part we read dystopias as syntheses of an evil that finds in a pervasive technology, outside any control by the human subjects who use it with trust, its irradiating fulcrum. Citizens can be subjugated to the technocratic power, only to the extent that they lose the ability to reflect critically and to confront each other in the freedom of dialogue. We believe that today’s despotic power resides, therefore, in the anti-formative use of digital computer technology, which functions as the Orwellian “Big Brother”, without the people being aware of it. Hence the need to revise not only the forms of education, but also the formative substance of politics, which appears increasingly anonymous, colourless and subject to the elusive will of financial interests, ready to use any mean without any respect for the democratic rules. The epistemological background is of the hermeneutic kind, the methodological approach is qualitative.